2014
DOI: 10.1098/rspb.2013.2694
|View full text |Cite
|
Sign up to set email alerts
|

Sexual conflict over mating in red-sided garter snakes (Thamnophis sirtalis) as indicated by experimental manipulation of genitalia

Abstract: Sexual conflict over mating can result in sex-specific morphologies and behaviours that allow each sex to exert control over the outcome of reproduction. Genital traits, in particular, are often directly involved in conflict interactions. Via genital manipulation, we experimentally investigated whether genital traits in red-sided garter snakes influence copulation duration and formation of a copulatory plug. The hemipenes of male red-sided garter snakes have a large basal spine that inserts into the female clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…However, females can adapt in more subtle ways if behavioral, physiological, or minor morphological modifications are sufficient to allow them to mitigate male inflicted damage, or to assert control over fertilization and mate identity. For example, in red-sided garter snakes (Thamnophis sirtalis sirtalis), females exert some physiological control over copulation duration; experimental anesthesia of the female vagina dramatically increased copulation duration (Friesen et al 2014). Conflict over copulation duration in garter snakes has likely resulted in modification and elaboration of male hemipene spines that allow males to stay attached to females for longer than optimal, as males with clipped spines stayed in copulo for a shorter period of time than intact males (Friesen et al 2014).…”
Section: Sexually Antagonistic Coevolution Resulting From Sexual Confmentioning
confidence: 99%
See 2 more Smart Citations
“…However, females can adapt in more subtle ways if behavioral, physiological, or minor morphological modifications are sufficient to allow them to mitigate male inflicted damage, or to assert control over fertilization and mate identity. For example, in red-sided garter snakes (Thamnophis sirtalis sirtalis), females exert some physiological control over copulation duration; experimental anesthesia of the female vagina dramatically increased copulation duration (Friesen et al 2014). Conflict over copulation duration in garter snakes has likely resulted in modification and elaboration of male hemipene spines that allow males to stay attached to females for longer than optimal, as males with clipped spines stayed in copulo for a shorter period of time than intact males (Friesen et al 2014).…”
Section: Sexually Antagonistic Coevolution Resulting From Sexual Confmentioning
confidence: 99%
“…Conflict over copulation duration in garter snakes has likely resulted in modification and elaboration of male hemipene spines that allow males to stay attached to females for longer than optimal, as males with clipped spines stayed in copulo for a shorter period of time than intact males (Friesen et al 2014). Copulation duration results from an interplay between male hemipene spines and female capacity to terminate copulation by contracting her vaginal musculature (Friesen et al 2014). This example highlights that the lack of overt specialized female structures that function to prevent male access cannot be used as evidence against the role of sexual conflict in genital evolution (contra Eberhard 2004Eberhard , 2006Eberhard , 2010b.…”
Section: Sexually Antagonistic Coevolution Resulting From Sexual Confmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be owing to the apparently greater frequency in males of morphological SA traits, which can be observed and measured with relative ease compared to behavioral and physiological traits. Classes of persistence traits include grasping appendages, ranging from the adhesive tarsae of diving beetles (Bergsten et al 2001) to the enlarged and spined and hooked antennae of water striders ; spiny stabbing genitalia in seed beetles (Crudgington and Siva-Jothy 2000), garter snakes (Friesen et al 2014), guppies (Fig. 2) (Kwan et al 2013) and traumatically inseminating bugs (Stutt and Siva-Jothy 2001;Tatarnic et al 2006); chemical traits, such as seminal proteins that influence female physiology and behavior (e.g., by boosting fecundity or delaying remating beyond the female optimum; Perry et al 2013), and behavioral traits, such as the harassment of females by males observed in many species.…”
Section: Male Sexual Armamentsmentioning
confidence: 99%
“…There are correlated patterns of evolution in male and female genital morphology that are consistent with this, including the thickening of the female reproductive tract (FRT) in response to the spined genitalia of male seed beetles ( Callosobruchus ) and the emergence of a female genital shield that protects against the grasping genitalia of male water striders ( Gerris ) . While sexual selection is known to be a pervasive force in the evolution of vertebrate genitalia, evidence of antagonistic coevolution via sexual conflict is considerably limited compared with the literature available on invertebrates …”
Section: Sexual Conflict: the Uneasy Alliance Between The Sexesmentioning
confidence: 93%